Small cell neuroendocrine carcinoma with adenocarcinoma and high grade squamous intraepithelial neoplasia of the cervix - Gurubalan, Guralarasan; Parwaiz, Amber; Ajit, Surabhi; Kumar, Tarun; Kumari, Madhu; Bhadani, Punam (Autopsy and Case Reports, 2023)
Neuroendocrine neoplasm (NEN) of the cervix is a malignant tumor and is classified into low and intermediate-grade neuroendocrine tumor (NET), and high-grade small cell neuroendocrine carcinoma (SCNEC), and large cells neuroendocrine carcinoma (LCNEC). SCNEC of the cervix is an Infrequent tumor with an incidence of less than 1% of all gynecological malignancies. It is characterized by small to medium-sized tumor cells with scant cytoplasm and neuroendocrine differentiation. Most cases of SCNEC of the cervix manifest in pure forms, and only cases show coexisting, non-neuroendocrine component of HPV-associated adenocarcinoma or squamous cell carcinoma. In this report, reviewing the literature, we present one such unique case of SCNEC of the cervix with adenocarcinoma and high-grade squamous intraepithelial neoplasia.